Current state of studies of the reception of Kant in Russian religious philosophy and its problems - Alexei Krouglov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
There are a number of difficulties and problems in contemporary studies of the perception of Kants philosophy in Russian religious philosophy. They pose serious problems for a comprehensive and thorough investigation of this theme. Firstly, it is the translation of outdated patterns. These patterns were formed at the turn of the nineteenth and twentieth centuries in first works of Russian Kantianism, written under the conditions of insufficient acquaintance with primary sources and refuted by the latest studies. However the results of these studies are ignored in significant layers of modern research literature. Second, it is an attempt to reduce Russian philosophy to Russian religious philosophy, and the latter mainly to the Soloviev and post-Soloviev period. Such a reduction excludes a huge number of personalities and works of Russian thinkers of the late eighteenth and nineteenth centuries. Thirdly, it is the presence of significant gaps in the knowledge of Kants reception in Russian religious philosophy, which still remain white spots. These lacunas and white spots prevent the creation of an adequate overall picture. They include the spread of Kantian philosophy in seminaries, the specific characteristic of reception of Kantian philosophy in the St. Petersburg, Moscow, Kiev, and Kazan Theological Academies, the reflection of Kantian philosophy on pages of printed editions of the Theological Academies, and the constancy or variation of evaluations of Kantian philosophy in emigration. Fourth, it is the ignorance of the reception of Kantian philosophy in Western European Protestantism, Catholicism, and Orthodoxy outside Russia. Such ignorance leads to a distorted assessment as uniquely Russian and Orthodox features of such philosophical aspects, which at different times have repeatedly taken place outside Russia as well. The goal of future research is to demonstrate the diversity of positions regarding Kantian philosophy in Russian religious philosophy, from categorical rejection to strong acceptance, taking into account the European Protestant, Catholic, and Orthodox contexts.